(untitled) (Al-Academy, 2023)
The current research dealt with the rapid development of industrial product design in recent times, and this development in the field of design led to the emergence of modern trends in many terms and theories to direct greater interest in the cognitive foundations of design and its relationship with the components of other natural sciences, and despite the impressive technological development, nature remains With its content of formative values and structural dimensions, it is the first source of inspiration and the source of all modern mathematical sciences and theories, as God made them tend towards organization to continue to provide us with endless inspiration. Hence, the fractional one, which is an important part of dedicating the design identity, as well as symmetry, complexity, self-organization and difference, and gives a new entrance and vision for the formation of forms characterized by complexity and of great importance to enrich the design process. The problem was identified by the following question: Defining the concept of fractionalism and its implications in the design of industrial products. The research included two important topics. We will address them successively.